Comparative Evaluation of Herbal Extract and Chlorhexidine as Root Canal Irrigants Against Enterococcus Faecalis- An In vitro Study - Prakash Kumar; Nitin Kararia; Manthena Srinivasa Raju (Journal of Pharmacy and Bioallied Sciences)
Background: Effective cleaning and adequate closure of the root canal are essential for successful endodontic therapy. Diverse pharmaceuticals, including both natural and synthetic alternatives, are used for disinfection purposes. This research sought to assess the antibacterial efficacy of herbal remedies (neem extract and tulsi extract) and chlorhexidine against Enterococcus faecalis in endodontics. Materials and Methods: The antibacterial efficacy was assessed using the agar diffusion technique. Forty samples were categorized into four groups, each including 10 samples: Group I–2% chlorhexidine, Group II–neem extract, Group III–tulsi extract, and Group IV–distilled water (control). The zones of inhibition for E. faecalis were quantified and evaluated by one-way analysis of variance (ANOVA) at a significant threshold of P < 0.05. Results: Of the evaluated medications, chlorhexidine demonstrated the most extensive zone of inhibition, followed by neem extract and tulsi extract. The control group (distilled water) had no antibacterial action. Statistical analysis revealed a substantial disparity in the antibacterial effectiveness across the groups (P < 0.05). Conclusion: Herbal medications, namely neem extract and tulsi extract, had considerable antibacterial efficacy against E. faecalis; nevertheless, chlorhexidine proved to be the most effective agent. Herbal options may function as viable supplements to traditional endodontic disinfectants.